Exploring benefits of speech and language therapy interventions for post-stroke aphasia rehabilitation: A qualitative study - Grace Larweh; Abena Asiedua Owusu Antwi; Ewurama Ampadu Owusu; Thomas Amatey Tagoe (Heliyon)
Background: The ability to understand and use language is impacted in people with aphasia, often requiring Speech and language therapy interventions to improve their ability to communicate. Currently, there is limited information concerning the experiences of people with aphasia who have undergone speech therapy in many countries such as Ghana where the practice of speech and language therapy is still in its infancy. Such knowledge is known to enhance the uptake of speech and language therapy services and improve both quality and reach. Objective: This study examines the perceived benefits of speech and language therapy interventions for people with aphasia in Ghana from the perspectives of those living with aphasia, their family members and Speech therapists. Additionally, this study sheds light on the interventions employed by Speech therapists in their pursuit of enhancing communicative competence among people with aphasia. Design: We employed a qualitative research design with a purposive sampling technique to recruit seven people with aphasia together with a family member and five Speech therapists. Participants: A total of 19 participants (7 people with aphasia, 7 family members and 5 Speech therapists) were recruited for this study. Methods: A semi-structured interview guide was used. Interviews were audio recorded, transcribed, and subjected to thematic analysis employing the Interpretative Phenomenological Analysis approach, to explore and comprehend the participants' lived experiences. Results: Our findings revealed that people with aphasia perceived speech and language therapy interventions to be beneficial as it enhanced their communication abilities as well as their quality of life. Family members of people with aphasia valued speech and language interventions as it gave them the opportunity to play a significant role in the recovery process of their family members with aphasia. Speech therapists described using a combination of impairment and functional/communication-based interventions to improve the communication skills and social participation of their clients with aphasia. Conclusions: Findings of the study indicate that people with aphasia and their caregivers experience significantly negative impact on their communication and quality of life, underscoring their profound appreciation for the relief provided by speech and language therapy interventions. Those who have undergone speech and language therapy interventions are inclined to recommend it to others due to its substantial benefits. This can be leveraged to increase the uptake of speech and language therapy and countries where the practise is still in its infancy.